(untitled) (Baghdad Science Journal, 2021)
The current study deals with the performance of constructed wetland (CW) incorporating a microbial fuel cell (MFC) for wastewater treatment and electricity generation. The whole unit is referred to as CW-MFC. This technique involves two treatments; the first is an aerobic treatment which occurs in the upper layer of the system (cathode section) and the second is anaerobic biological treatment in the lower layer of the system (anode section). Two types of electrode material were tested; stainless steel and graphite. Three configurations for electrodes arrangement CW-MFC were used. In the first unit of CW-MFC, the anode was graphite plate (GPa) and cathode was also graphite plate (GPc), in the second CW-MFC unit, the anode was stainless steel mesh (SSMa) and the cathode was a couple of stainless steel plain (SSPc). The anode in the third CW-MFC unit was stainless steel mesh (SSMa) and the cathode was graphite plate (GPc). It was found that the maximum performance for electricity generation (9 mW/m3) was obtained in the unit with stainless steel mesh as anode and graphite plate as cathode. After 10 days of operation, the best result for COD removal (70%) was obtained in the unit with stainless steel mesh as anode and stainless steel plain as cathode. The effect of temperature was also investigated. The performance of unit operation for electricity generation was tested at three values of temperature; 30, 35 and 40oC. The best result was obtained at 40oC, at which the current density obtained was 80 mA/m3. A culture of Algae could grow in the unit in order to supply the cathodic region with oxygen.